Case Report: Exome Sequencing Identified Variants in Three Candidate Genes From Two Families With Hearing Loss, Onychodystrophy, and Epilepsy - Li, Yuan; Xiong, Jianjun; Zhang, Yi; Xu, Lin; Liu, Jianyun; Cai, Tao (Frontiers in Genetics, 2021)
A cohort of 542 individuals in 166 families with congenital hearing loss was recruited for whole-exome sequencing analysis. Here we report the identification of three variants in five affected individuals in two unrelated families. In family 1, a nonsense mutation (c.1516C>T, p.R506*) in the ATP6V1B2 gene, a known causal allele for dominant deafness-onychodystrophy (DDOD), was identified in the mother and son with DDOD. However, a novel heterozygous variant (c.632G>A, p.D530E) in TJP2, a known causal gene for hearing-loss, was also detected in the patients. In family 2, the same mutation (c.1516C>T, p.R506*) of ATP6V1B2 was detected from the father and daughter with DDOD. Furthermore, a novel heterozygous variant (c.733A>G, p.M245V) in the KIF11 gene was identified from the spouse with sensorineural hearing-loss and epilepsy. Notably, genotype-phenotype analysis of KIF11-associated disorders revealed that the p.M245V and two reported hearing-loss-associated variants (p.S235C and p.H244Y) are all mapped to a single beta-sheet (Ser235-M245) in the kinesin motor domain. Together, this is first demonstration that ATP6V1B2-caused DDOD is an autosomal dominant genetic disease, compared to previous cases with de novo mutation. Our findings expand the variant spectrum of hearing-loss-associated genes and provide new insights on understanding of hearing-loss candidate genes ATP6V1B2, TJP2, and KIF11.